Insight Into Pituitary lncRNA and mRNA at Two Estrous Stages in Small Tail Han Sheep With Different FecB Genotypes - Chen, Si; Guo, Xiaofei; He, Xiaoyun; Di, Ran; Zhang, Xiaosheng; Zhang, Jinlong; Wang, Xiangyu; Chu, Mingxing (Frontiers in Endocrinology, 2022)
The pituitary is a remarkably dynamic organ with roles in hormone (FSH, LH) synthesis and secretion. In animals with the FecB mutation, the pituitary experiences hormone fluctuations during the follicular–luteal transition, which is implicated in the expression and regulation of many genes and regulators. Long non-coding RNAs (lncRNAs) are a novel type of regulatory factors for reproductive process. Nevertheless, lncRNA expression patterns and their roles in FecB-mediated follicular development and ovulation remain obscure. Thus, we profiled the pituitary transcriptome during the follicular (F, 45 h after evacuation vaginal sponges at) and luteal (L, 216 h after evacuation vaginal sponges) phases in FecB-mutant homozygous (BB) and wild-type (WW) Small Tail Han sheep. We identified 78 differentially expressed genes (DEGs) and 41 DE lncRNAs (DELs) between BB_F and BB_L, 32 DEGs and 26 DELs between BB_F and WW_F, 16 DEGs and 29 DELs between BB_L and WW_L, and 50 DEGs and 18 DELs between WW_F and WW_L; qRT–PCR results correlated well with the transcriptome data. In both the follicular and luteal phases, DEGs (GRID2, Glutamate Ionotropic Receptor Delta Type Subunit 2, ST14, ST14 Transmembrane Serine Protease Matriptase) were enriched in hormone synthesis, secretion and action. MSTRG.47470, and MSTRG.101530 were trans-regulated elements of Inhibitor of DNA Binding 3, HLH Protein (ID1) and of DEG Inhibitor of DNA Binding 3, HLH Protein (ID3), and Eukaryotic Translation Elongation Factor 2 (EEF2), respectively; these factors might be involved in melatonin and peptide hormone secretion. In the FecB-mediated follicular phase, MSTRG.125392 targeted Seizure Related 6 Homolog Like (SEZ6L) and MSTRG.125394 and MSTRG.83276 targeted the DEG Potassium Voltage-Gated Channel Subfamily Q Member 3 (KCNQ3) in cis, while MSTRG.55861 targeted FKBP Prolyl Isomerase 4 (FKBP4) in trans. In the FecB-mediated luteal phase, LOC105613905, MSTRG.81536, and MSTRG.150434 modulated TGFB1, SMAD3, OXT, respectively, in trans. We postulated that the FecB mutation in pituitary tissue elevated the expression of certain genes associated with pituitary development and hormone secretion. Furthermore, this study provides new insights into how the pituitary regulates follicular development and ovulation, illustrated by the effect of the FecB mutation.